A modified approach to improve the performance of AES using feistel structure - Al-Ansi, Afeef Yahya Ahmed (2018)
In encryption algorithm design, apart from the security performance, processing performance and the cost of the implementation are very important trade-off parameters. A most popular and widely adopted symmetric encryption algorithm is the Advanced Encryption Standard (AES). It suffers from the demand for the performance efficiency. To improve its computational cost, we propose a modification of the AES technique. Having found that out of the four major operations in the AES; MixColumn is the one that takes huge amount of computing time and for which replacement with look-up table adds additional space constrain, we propose replacing the MixColumns with a Feistel Structure that exits and is the main engine of the Data Encryption Standard (DES). Empirical performance analysis on our proposed modified AES shows a significant reduction in the processing time by up to 67% on the average. The method support parallel implementation with little overhead.